Design of New Business Models for REBEL 504 In Surakarta City by Using Business Model Canvas Approach - Yoga Widagda Wendy Pradhana; Budi Praptono; Boby Hera Sagita (eProceedings of Engineering, 2019)
Abstract REBEL 504 is family-based organizations that provide security services with a strong commitment to our customers to provide the best service for each customer's needs. Just a note that the current REBEL 504 to serve multiple customer segment in the field of safeguard, bodyguard, security/event/music art festival, a Porter, and street fight. REBEL 504 can be said to have not been managed by professionals. A business or businesses are already supposed to be managed with the serious and professional in order for the purpose of doing business can be achieved to the maximum. Therefore, required the design of appropriate and in accordance with the objectives or purpose of the business. One of the business models that can be run is a business model canvas. View of the problems occurred in the REBEL 504, then needed an approach that can be used to map the business model that is being lived, and explains about the condition of the company's business, so that new business models can be designed. One approach to business models that can be used i.e. Business Model Canvas (BMC). This research resulted in the proposal of the strategy has been designed and will be on view is valid or whether to find out the profit that would be obtained if the company implements the proposal. The business model is designed to use nine blocks including the BMC Customer Segment, Value Proposition, Channels, Customer Relationship, Revenue Streams, Cost Structure, Key Activity, Key Partnership, Key Resources. Keywords: Business Model Canvas, SWOT, Business Model